Evaluasi Dan Perbaikan Desain Antarmuka Pengguna Situs Web Pariwisata Dengan Menggunakan Pendekatan User Centered Design (UCD) (Studi Kasus : Balai Besar Taman Nasional Bromo Tengger Semeru Malang) - Rizky Nur Rochman; Retno Indah Rokhmawati; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The website of Bromo Tengger Semeru National Park becomes an influential tourism website for some users, one of which is climber. But 5 climber as well as users still have difficulty understanding the content of this website, because the user interface is still difficult to understand such as the font size is too small, then irregular content, and inconsistent language. So this website is still far from usability aspect. To generate a website with user-understandable interface, a User Centered Design (UCD) approach is used which will involve the user in the development process. There are 5 climbers who became respondents in this research. In this research also use 3 usability aspect that is aspect of effectiveness, efficiency, and user satisfaction. Aspects of effectiveness and efficiency using user tasks. Full Scale Task Scenario, while the user satisfaction aspect uses PSSUQ questionnaire. These three aspects will be used for evaluation of the website before and after improvement. Comparative results during the evaluation before and after the improvement have increased. On the effectiveness aspect, the percentage of success increased by 4%, the efficiency aspect increased as much as 37.13 seconds, and the user satisfaction aspect increased as much as 37.7%.